Effects of dynamic elongational flow on the dispersion and mechanical properties of low‐density polyethylene/nanoprecipitated calcium carbonate composites. Issue 5 (31st October 2013) - Jia, Shikui; Qu, Jinping; Zhai, Shufeng; Huang, Zan; Wu, Chengran; Chen, Rongyuan; Feng, Yanhong
<x xml:space="preserve">Abstract</x> Low‐density polyethylene (LDPE)/nanoprecipitated calcium carbonate (NPCC) nanocomposites were prepared with a self‐made vane extruder (VE) that generates global dynamic elongational flow and with a single‐screw extruder (SSE) that generates low shear flow. The mechanical properties, dispersed phase morphology, and thermal behavior of the nanocomposites were investigated to compare the different processing techniques. Scanning electron micrograph and transmission electron micrograph show that the elongational flow in the VE improves the dispersion of NPCC (5 wt%) particles in the LDPE matrix. The dimensional distribution of NPCC particles in the VE is significantly lower than that of the SSE. Differential scanning calorimetric curves indicate that dynamic elongational flow can enhance the crystallization ability of the LDPE/NPCC nanocomposites. The mechanical properties of the VE‐extruded samples are superior to those of the SSE‐extruded samples. When compared with that of SSE, morphology of tensile fracture surfaces suggests that the uniform and fine dispersion of NPCC particles in the LDPE matrix can successfully improve modulus and toughness of the LDPE/NPCC nanocomposites based on the novel VE. POLYM. COMPOS., 35:884–891, 2014. © 2013 Society of Plastics Engineers